STRENGTH DEVELOPMENT IN HYPOTONIC CHILDREN FROM AN EDUCATIONAL SWIMMING WORK: A CASE STUDY (Fiep Bulletin - online, 2016)
Hypotonia is a condition that leads the child to present a physical weakness table by decreasing muscle strength in holding force. Swimming is a physical activity that promotes the development of various physical abilities in the performance of motor actions during the teaching process. Objective: To determine whether an educational swimming program is efficient and effective to induce force levels increases in children with hypotonia. Method study is qualitative, quasi-experimental, field, shows two subjects: S1, 6 years, boy, S2, 8, girl, diagnosed with hypotonia. Educational program of swimming twice a week, with 60 minutes each section, 16 weeks. Tests to measure strength (Eurofit): the upper (hanging on the bar), trunk (maximum load lying in elbow extension) and lower (standing long jump), pre and post test; weight record (S1 and S2 37kg 35kg) and height; anecdotal record. Results: pre-test negative to support body weight with upper limbs on both subjects; standing long jump: S1, S2 and 24cm, 26cm. Post-test: the two subjects were able to maintain body weight by 4 seconds (S1) and 6/2 (s2); Power increase in the lower limbs. Conclusions: results for upper limbs were higher than the results for lower limbs, considering the specifics of natação.Com the improvement of physical capacity, other variables are influenced, as the social aspects and personal development. The use of a swimming program without considering a special work for strength development was efficient and effective to induce the development of strength in the subject.
Keywords: hypotonia; swimming; children.